Creating a Physical Environment in Community Public Spaces to Facilitate and Improve the Quality of Life of Elderly People : A Case Study of Kradang Nga Sub-district, Samut Songkhram - Pongthana, Phattita (Journal of Cultural Approach, 2022)
Creating a physical environment is important for the elderly. They have a decreased ability to control their environments, such as the ability to overcome oppression, stress, and lifestyle changes. For this reason, creating a suitable environment to facilitate and improve their quality of life is essential for the elderly. Therefore, Kradang Nga municipality and the Bang Noi community have recognized the importance of providing a physical environment and facilities for the elderly in public areas that support their lifestyle and community context. The objective of this research is to establish guidelines for designing and improving the physical environment and facilities in the community to facilitate and promote the quality of life of the elderly. The researchers also did a physical site survey and in-depth interviews with local stakeholders and related agents to design the guidelines for developing the physical environment and facilities for the elderly in the community. Therefore, the overall guidelines for the physical environment management and facilities can support and respond to the needs of the community. Furthermore, it is beneficial for tourists of all ages in Bang Noi floating market.